“You don’t want to buy it, you want to borrow it” : humour in the Prince Edward Island auctioneer’s performance - Thurgood, Ranald (Ethnologies, 1994)
Auctioneers in eastem Prince County, Prince Edward Island are entertainers as well as salesmen. They continually interrupt their rhythmic speech to joke with their audiences. Though most of their wit is spontaneous, the auctioneer’s use of humour is quite conscious and has pragmatic functions - to sell goods and to achieve social control over their audiences. This paper examines the use of humour by auctioneers of farm and household goods and shows how their humour reflects the values of their society.